PELANGGARAN PRINSIP KEHATI-HATIAN DALAM HILANGNYA DANA NASABAH BANK SULSELBAR: Violation of the Prudential Principle in the Loss of Bank Sulselbar Customer Funds - Al Rabbani, Muhammad Irfan; Setyaningsih (Faculty of Law, Universitas Trisakti, 2025)
Violations of the precautionary principle in the case of lost customer funds at Bank Sulselbar. Banks are responsible for maintaining liquidity and public trust by implementing the precautionary principle. However, the phishing case in Bank Sulselbar's mobile banking service shows that the bank did not apply the precautionary principle by not blocking hacked customer accounts. As a result, the customer lost Rp. 131.485.906 while the bank only offered compensation of Rp. Rp.45.479.406. This research found that Bank Sulselbar violated Article 29 paragraph (2) of Law No. 10/1998 concerning Banking and Article 20A Paragraph (1) of Law No. 4/2023 concerning Development and Strengthening of the Financial Sector. That the method used in this research is to use normative research methods carried out on legal principles related to the subject of the research, in this case the violation of the precautionary principle in the loss of funds from Bank Sulselbar customers. The conclusion is that negligence in implementing the precautionary principle causes significant losses for customers and damages public trust in banks. That banks must increase security and maintain public trust by tightening operational procedures and improving risk management systems to prevent similar incidents in the future.